2022
DOI: 10.1080/16549716.2021.2021631
|View full text |Cite
|
Sign up to set email alerts
|

HIV self-testing for men who have sex with men in Sweden. A cross-sectional study concerning interest to use HIV self-tests

Abstract: Background HIV self-testing (HIVST) has been found to have high acceptability among men who have sex with men (MSM) internationally and might contribute to increase testing frequencies, but many countries, including Sweden, lack policies for using HIVST. Objective To examine interest to use and willingness to pay for HIVST, and associated factors, among MSM attending HIV testing venues in Sweden. Method This cross-sectional study analyzed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Consistent with previous findings, our study showed that MSM with high-risk sexual behaviors have a lower willingness to test for HIV [ 15 17 ]. As a result, MSM who engage in hazardous sexual activity and are sexually active should be the focus of HIV prevention education, which is essential for lowering HIV incidence.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous findings, our study showed that MSM with high-risk sexual behaviors have a lower willingness to test for HIV [ 15 17 ]. As a result, MSM who engage in hazardous sexual activity and are sexually active should be the focus of HIV prevention education, which is essential for lowering HIV incidence.…”
Section: Discussionsupporting
confidence: 92%
“…Investigators focusing on the high-risk population's (MSM) HIV-testing behavior in China during the COVID-19 pandemic found the use of HIV self-testing increased compared to facility-based HIV testing, which decreased by more than 50% overall [26,27]. Earlier investigations in Sweden and Japan showed the interest and demand for HIV self-testing in high-risk populations such as MSM even before the COVID-19 pandemic [12,28]. A study in France also reported that the number of HIV self-testing kits sold in 2021 increased by 3% compared to 2020 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Global public health system is facing a huge challenge of in HIV prophylaxis and control. The proactive detection of HIV is critical to cut off the transmission and end the pandemic [ 44 ]. However, young students are less likely to uptake HIV testing, though they have a greater risk of exposure [ 45 ].…”
Section: Discussionmentioning
confidence: 99%